1992
DOI: 10.1111/j.1442-9071.1992.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of experimental chronic intraocular hypertension in the rabbit

Abstract: There are many unanswered questions about chronic glaucoma which cannot be investigated in the available animal models. The present experiments were designed to develop a rabbit model of chronic intraocular hypertension with characteristics similar to human chronic glaucoma by ligating vortex veins or by making single or multiple intraocular injections of 0.5% or 1% a-chymotrypsin, 20% chondroitin sulphate, 2% hydroxypropyl methylcellulose, 2% sodium carboxymethylcellulose or 1% or 2% methylcellulose. Evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
4
20
0
4
Order By: Relevance
“…It has been shown that the intracameral administration of CS increases IOP in cats but not in rabbits. 44 However, though repeated injections of CS (9 mg/eye) into the cat anterior chamber increase 4 to 7 mm Hg above that of control eyes, an almost 100% (ϳ10 mm Hg) increase was observed in rat eyes injected with CS (8 mg/eye) compared with vehicleinjected eyes. Because the rat eye anterior chamber is very shallow, the higher hypertension provoked by CS in the rat than in the cat eye could be attributed to the fact that actual intracameral concentrations of CS in the rat eye should be higher than those achieved in the cat eye.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that the intracameral administration of CS increases IOP in cats but not in rabbits. 44 However, though repeated injections of CS (9 mg/eye) into the cat anterior chamber increase 4 to 7 mm Hg above that of control eyes, an almost 100% (ϳ10 mm Hg) increase was observed in rat eyes injected with CS (8 mg/eye) compared with vehicleinjected eyes. Because the rat eye anterior chamber is very shallow, the higher hypertension provoked by CS in the rat than in the cat eye could be attributed to the fact that actual intracameral concentrations of CS in the rat eye should be higher than those achieved in the cat eye.…”
Section: Discussionmentioning
confidence: 96%
“…En cuanto a las CGR, los análisis descriptivos de los preparados histológicos (fig 4 b), demostraron una pérdida de las mismas, pero no se pudo concluir ni la velocidad, ni el porcentaje de pérdida, ya que el período de HTO fue muy corto: 24 hs. Otra técnica empleada para aumentar la PIO en modelos animales es mediante la inyección de α-quimotripsina en la cámara posterior del ojo 21,22 . Si bien no es un procedimiento utilizado actualmente para inducir glaucoma, la utilización de este modelo en nuestro caso demostró diferentes resultados a los hallados en el modelo A. El aumento de la PIO fue de aproximadamente un 130%, estable y con un pico de 35 mmHg a las 3 semanas de la inducción.…”
Section: Discussionunclassified
“…In addition, the side effects of the antiseptic and emulsifying agents in the suspension must be considered. [12][13][14][15][16] There was no IOP increase in our patients, which indicates intracameral triamcinolone acetonide might not induce an IOP increase when the triamcinolone acetonide granules and preservative are sufficiently removed. In our series, intracameral triamcinolone acetonide in the management of vitreous loss during phacoemulsification was not related to postoperative endophthalmitis during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%